HHV-8 and EBV-positive intravascular lymphoma: an unusual presentation of extracavitary primary effusion lymphoma - Crane, Genevieve M. (2014)
Intravascular lymphomas are rare and aggressive hematolymphoid tumors. Here we describe a human herpesvirus type-8/Kaposi sarcoma-associated herpesvirus (HHV-8/KSHV) and Epstein-Barr virus (EBV) positive intravascular lymphoma. The patient was a 59 year-old HIV-positive man who presented with diarrhea, abdominal pain, fevers, night sweats, and weight loss. Radiographic studies of the abdomen and pelvis revealed numerous subcentimeter nodules within the subcutaneous fat that lacked connection to the skin. An excisional biopsy demonstrated large atypical cells within vessels in the deep subcutaneous fat, and many of the vessels contained extensive organizing thrombi. The atypical cells lacked strong expression of most B-cell markers but were positive for MUM-1 and showed partial expression of several T-cell markers. An immunohistochemical stain for HHV-8 and an in situ hybridization for EBV were both positive in the neoplastic cells. The disease had a rapidly progressive and fatal course. This lymphoma appears to represent an entirely intravascular form of primary effusion lymphoma, and highlights the propensity for HHV-8 and EBV-positive lymphoid neoplasms to show aberrant expression of T-cell markers, illustrates the utility of skin biopsies for the diagnosis of intravascular lymphoma, and suggests that biopsies to evaluate for intravascular lymphoma should be relatively deep and include subcutaneous fat.